PENGEMBANGAN MEDIA PEMBELAJARAN FLASHCARD BERBASIS HOTS PADA MATERI PECAHAN KELAS V DI SEKOLAH DASAR - Retno Ayu; Riawan Yudi Purwoko; Arum Ratnaningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the limited learning media, students have difficulty in understanding the material, students cannot solve the questions given, fractions are considered difficult by students, and the boring learning atmosphere makes students more passive. This study aims to develop flashcard learning media, and determine the feasibility of flashcard media. This study uses the R&D (Research and Development) method using the ADDIE model which consists of stages, namely analysis, design, development, implementation and evaluation. The results of this HOTS-based flashcard media development research are 1) HOTS-based flashcard media using the ADDIE model. The analysis stage produces flashcard media for fractions, the design stage produces flashcard designs, the development stage validates flashcard media, the implementation stage carries out limited trials and extensive trials, the evaluation stage carries out evaluation of flashcard media development; 2) The feasibility of flashcard media is carried out by media experts and material experts. The assessment by media experts showed an average score of 75%, while the assessment by material experts got an average score of 78.6% which is classified as valid. Practicality by student responses showed an average result of 100%, which is classified as very practical, then the effectiveness assessment from the results of extensive trials showed an average N-gain of 0.72 which is classified as a high increase. Based on this study, it can be concluded that flashcard media is suitable for use in learning.